WORKING ON AND CONFIRMING A SCALE TO MEASURE SELF-EFFICACY IN PEDIATRIC CLINICAL DECISION-MAKING - Dr Pallavi; Dr Saginala Ravichandra; G Harsha Vardhan Kumar; D Jothieswari (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
To succeed in clinical practice, people need to have both the knowledge and ability, plus the belief in their ability to carry out needed tasks. No present tool is designed solely for measuring self-efficacy during clinical decisions common in general pediatrics. In order to measure pediatric residents’ confidence in making clinical choices in general pediatric settings, an updated scale called the General Pediatrics-specific Self-Efficacy (GPedsSE) scale was created and tested. Experts created a five-item GPedsSE scale, patterned after the New General Self-Efficacy (NGSE) scale, to make it easy to compare the two. All the pediatric residents in postgraduate years 1 through 5 at the tertiary center completed both scales and the items were mixed order to cut down on bias. GPedsSE scores averaged 18.6 (with an average deviation of 2.6), out of a total score of 25. A correlation of 0.54 (P < 0.005) was found between GPedsSE and NGSE scores. GPedsSE improved a lot through different levels of training (F[1.3] = 6.62; P < 0.001), while NGSE did not change much (F < 0.37). Each scale was clearly found to consist of two components through factor analysis. GPedsSE can help you measure your confidence in making decisions when caring for children. This development proposes a new method to prove concurrent validity by taking an existing general tool and making it fit for specialty use.